Genetic polymorphism of KIR2DL4 in the Polish population. Issue 6 (27th March 2015) - Nowak, I.; Barcz, E.; Majorczyk, E.; Malinowski, A.; Wilczyński, J. R.; Banasik, M.; Motak‐Pochrzęst, H.; Kuśnierczyk, P.
Abstract The KIR2DL4 gene is characterized by alleles with either 9 or 10 consecutive adenines in exon 7, which encodes the transmembrane domain. The 9A variant produces either a protein with a truncated cytoplasmic tail or one lacking the transmembrane region. This causes a lack of KIR2DL4 expression. In contrast, 10A alleles encode receptors that may be expressed at the cell surface. We tested 438 healthy individuals for polymorphism of the KIR2DL4 gene. KIR2DL4 9A/10A alleles were distinguished by the high resolution melting (HRM) method, and restriction fragment length polymorphism (RFLP) was used for genotyping of three other single nucleotide polymorphisms (SNPs) spanning the near vicinity of the poly‐adenine fragment. We found a weak difference between males and females in 9769 C/A genotypes and alleles. In addition, we observed complete linkage disequilibrium (LD) between 9A insertion/deletion in the 9620 position and the 9571T/C position of the gene (r2 = 1) both in females and males and almost complete LD with the 9797G/A position (r2 = 0.963 for females and r2 = 0.892 for males). Most importantly, we detected, in a group of fertile women, a high frequency (30.2%) of homozygosity for the defective 9A variant, which suggests that KIR2DL4 as a functional cell surface receptor is not absolutely necessary for reproduction. On the other hand, lower representation of 10A/10A homozygotes and high frequency of 10A/9A heterozygotes indicates a need for both cell membrane‐anchored and soluble KIR2DL4 molecules. Finally, cost‐reducing RFLP instead of HRM is proposed for typing 9A and 10A variants.